Titanium-Doped Diamond-like Carbon Layers as a Promising Coating for Joint Replacements Supporting Osteogenic Differentiation of Mesenchymal Stem Cells - Travnickova, Martina; Filova, Elena; Slepicka, Petr; Slepickova Kasalkova, Nikola; Kocourek, Tomas; Zaloudkova, Margit; Suchy, Tomas; Bacakova, Lucie (International journal of molecular sciences, 2024)
Diamond-like carbon (DLC) layers are known for their high corrosion and wear resistance, low friction, and high biocompatibility. However, it is often necessary to dope DLC layers with additional chemical elements to strengthen their adhesion to the substrate. Ti-DLC layers (doped with 0.4, 2.1, 3.7, 6.6, and 12.8 at.% of Ti) were prepared by dual pulsed laser deposition, and pure DLC, glass, and polystyrene (PS) were used as controls. In vitro cell-material interactions were investigated with an emphasis on cell adhesion, proliferation, and osteogenic differentiation. We observed slightly increasing roughness and contact angle and decreasing surface free energy on Ti-DLC layers with increasing Ti content. Three-week biological experiments were performed using adipose tissue-derived stem cells (ADSCs) and bone marrow mesenchymal stem cells (bmMSCs) in vitro. The cell proliferation activity was similar or slightly higher on the Ti-doped materials than on glass and PS. Osteogenic cell differentiation on all materials was proved by collagen and osteocalcin production, ALP activity, and Ca deposition. The bmMSCs exhibited greater initial proliferation potential and an earlier onset of osteogenic differentiation than the ADSCs. The ADSCs showed a slightly higher formation of focal adhesions, higher metabolic activity, and Ca deposition with increasing Ti content.
Keywords: Cell Differentiation; uhlík; povrchové vlastnosti; Mesenchymal Stem Cells; osteogenic differentiation; biocompatibility; Osteogenesis; Titanium; Carbon; mezenchymální kmenové buňky; Surface Properties; osteogeneze; bone marrow mesenchymal stem cells (bmMSCs); artroplastiky kloubů; diamond-like carbon layer (DLC); buněčná diferenciace; titanium; adipose tissue-derived stem cells (ADSCs); titan; Arthroplasty, Replacement